Expression of Estrogen and Progesterone Receptors in Papillary Thyroid Carcinoma - Mohammadreza Jalali-Nadoushan; Reza Amirtouri; Ali Davati; Samaneh Askari; Sepideh Siadati (Caspian Journal of Internal Medicine, 2016)
Background: Papillary thyroid carcinoma (PTC), occurs mostly in women and sex hormones may play a role in the pathogenesis and clinical course. The objective of this study was to determine the status and prevalence of estrogen and progesterone receptors in PTC with regard to age, gender, tumor size and lymph node involvement.